Effectiveness of physiological flexion swaddling and oromotor interventions in improving preterm infants' oral feeding ability in the NICU: a randomized controlled trial - Luh K. Wahyuni; Irawan Mangunatmadja; Risma K. Kaban; Elvie Zulka K. Rachmawati; Rizky K. Wardhani; Budiati Laksmitasari; Boya Nugraha (Jornal de Pediatria)
Objective: This study aimed to prove the effectiveness of physiological flexion swaddling and oromotor interventions in terms of the duration needed to achieve the oral feeding ability of preterm infants in the NICU. Methods: A randomized clinical trial in five Neonatal intensive care units (NICU) was performed involving 70 preterm infants born at 28–34 weeks gestational age. Participants were allocated to 1) the experimental group (n = 39) received physiological flexion swaddling and oromotor interventions, and 2) the control group (n = 31) received conventional swaddling and oromotor interventions. Mann-Whitney U analysis was used to determine the effectiveness of each group according to the duration needed to achieve oral feeding ability, while Kaplan-Meier survival analysis was applied to compare the duration of both groups. Results: The experimental group had a significantly shorter duration in achieving oral feeding ability [4 (1–15) vs. 7 (2–22) days; p = 0.02]. The Kaplan-Meier survival curve analysis showed that infants in the experimental group achieved full oral feeding ability earlier than those in the control group (15 vs. 22 days). Conclusions: Physiological flexion swaddling and oromotor interventions have been proven to be effective in shortening the number of days needed to achieve the oral feeding ability of preterm infants in the NICU.